2022
DOI: 10.1097/ijg.0000000000002129
|View full text |Cite
|
Sign up to set email alerts
|

Two Year Randomized Prospective Comparison of Ahmed Valve Versus Baerveldt Implant in Vitrectomized Eyes

Abstract: Précis: Ahmed Valve and Baerveldt shunt are efficacious options in vitrectomized eyes. Baerveldt implant achieves a lower mean intraocular pressure (IOP) at 2 years, with fewer medications and a higher percentage of medication-free patients.Purpose: To investigate and compare the efficacy and complications between Ahmed FP7 Glaucoma Valve (AGV) and Baerveldt 101-350 Glaucoma Implant (BGI) in vitrectomized eyes. Materials and Methods:In this single-center randomized clinical trial, 43 vitrectomized eyes (39 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Many published studies have reported the effectiveness and safety of AGVI in vitrectomized eyes with different indications for PPV (17)(18)(19)(20)(21). However, AGVI results may vary depending on etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Many published studies have reported the effectiveness and safety of AGVI in vitrectomized eyes with different indications for PPV (17)(18)(19)(20)(21). However, AGVI results may vary depending on etiology.…”
Section: Discussionmentioning
confidence: 99%